Benin : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper analyzes the growth, structural transformation, and export diversification in Benin. Although Benin has delivered high economic growth over recent years, it faces critical challenges regarding export diversification and domestic production. Benin's competitiveness is impaired by structural bottlenecks. Low and stagnant productivity in the agriculture sector is perhaps a primary cause of the limited poverty reduction in rural areas. Policies to promote structural transformation and diversification should focus on addressing weaknesses that hinder entry into new lines of economic activity. Further progress on strengthening the business climate, addressing electricity shortages, and increasing human capital could provide significant benefits.